Keith Douglas: War Poet - Shearer, William James (My University, 1970)
The dilemma of the war poet -- how "to combine two incompatibles" -- has produced several temporary alternatives and as many permanent misconceptions. For some, writers and audience alike, war poetry has come to be merely a form of propaganda, or perhaps an outlet for the emotions. For Keith Douglas, however, war was apparently a natural and a compatible subject for poetry. This study focuses upon Douglas's life, work and reputation, in an attempt to discover how, why, and to what effect he was able to solve the dilemma.
Keywords: dilemma, war, poet, propaganda